DA'WAH STRATEGY OF SULAIMANIYAH PESANTREN IN INSTILLING AKHLAQUL KARIMAH MAHASANTRI: (Study on Sulaimaniyah Islamic Boarding School for Sultan Students) Selahaddin Banda Aceh) - Ridwan Muhammad Hasan Ridwan Muhammad Hasan; Maulana Arifan (STAI Nusantara Kota Banda Aceh, 2025)
The progress of the times has caused many young people to stray from Islamic values, especially akhlaqul karimah. Institutions such as Islamic boarding schools are needed as a solution to minimise and even change this gap, transforming it in accordance with Islamic values themselves. A wise strategic process is required to successfully produce young people who are Islamic and possess akhlaqul karimah. This study is titled